Descriptive analysis of students’ CGPA: a case study of Universiti Malaysia Pahang - Roslinazairimah, Zakaria; Siti Zanariah, Satari; Rozieana, Khairuddin; Nor Alisa, Mohd Damanhuri (2018)
This study presents the descriptive analysis of students’ performance based on the cumulative grade point average (CGPA) of the entry grade and the CGPA achieved throughout their study duration until graduation. The data analysed are from all bachelor degree program students at Universiti Malaysia Pahang of 2011, 2012 and 2013 cohorts. Components which affect the academic performance are analysed such as gender, entry qualification, entry CGPA, academic program and cohort. The results show that students from Sijil Tinggi Pelajaran Malaysia (STPM) performs very well academically with mean CGPA of 3.30 throughout the study period as compared to students from diploma (CGPA:2.97), matriculation (CGPA:2.88) or Sijil Tinggi Agama Malaysia (STAM; CGPA:2.71). Gender factor do not has significant effect on students’ academic performance.